Hemin binding by Porphyromonas gingivalis strains is dependent on the presence of A‐LPS. (9th March 2017) - Rangarajan, M.; Aduse‐Opoku, J.; Paramonov, N.A.; Hashim, A.; Curtis, M.A.
Abstract : Porphyromonas gingivalis is a Gram‐negative black pigmenting anaerobe that is unable to synthesize heme [Fe(II)‐protoporphyrin IX] or hemin [Fe(III)‐protoporphyrin IX‐Cl], which are important growth/virulence factors, and must therefore derive them from the host. Porphyromonas gingivalis expresses several proteinaceous hemin‐binding sites, which are important in the binding/transport of heme/hemin from the host. It also synthesizes several virulence factors, namely cysteine‐proteases Arg‐ and Lys‐gingipains and two lipopolysaccharides (LPS), O‐LPS and A‐LPS. The gingipains are required for the production of the black pigment, μ‐oxo‐bisheme [Fe(III)PPIX]2 O, which is derived from hemoglobin and deposited on the bacterial cell‐surface leading to the characteristic black colonies when grown on blood agar. In this study we investigated the role of LPS in the deposition of μ‐oxo‐bisheme on the cell‐surface. A P. gingivalis mutant defective in the biosynthesis of Arg‐gingipains, namely rgpA/rgpB, produces brown colonies on blood agar and mutants defective in Lys‐gingipain ( kgp ) and LPS biosynthesis namely porR, waaL, wzy, and pg0129 (α‐1, 3‐mannosyltransferase) produce non‐pigmented colonies. However, only those mutants lacking A‐LPS showed reduced hemin‐binding when cells in suspension were incubated with hemin. Using native, de‐ O ‐phosphorylated and de‐lipidated LPS from P. gingivalis W50 and porR strains, we demonstrated that hemin‐binding to O‐polysaccharide (PS) and to the lipid A moiety of LPS was reduced compared with hemin‐binding to A‐PS. We conclude that A‐LPS in the outer‐membrane of P. gingivalis serves as a scaffold/anchor for the retention of μ‐oxo‐bisheme on the cell surface and pigmentation is dependent on the presence of A‐LPS.